DEVELOPMENT OF COMPLEX SOCIUM: A HUMANISTIC TURN - S. A. Kravchenko (Vestnik MGIMO-Universiteta)
The author analyzes new vulnerabilities appeared as a result of the becoming of the complex socium that has become a topical subject of debate in social science. It is shown that these vulnerabilities manifest new risks for the functioning of the society and its members. The self-sufficiency of the modern society is in real danger: the formation of a complex society passed the barrier, after which the viability of the society is by no means guaranteed. On the one hand, society can hardly keep up with the increasing chaos of values and normative referents , undermining its internal functioning adequately, on the other hand, it is obvious that the relationship between social and natural systems significantly impaired. There appeared vulnerabilities in the form of unintended consequences of the openness of the society, that increases the production of new marginalized groups – people who are not temporarily unemployed, but those who do not adapt to the cultural innovations of the open society. The complex socium has the potential of new catastrophes provoked by “normal accidents”. For solving these problems there proposed a humanistic turn that presupposes the integration of Sociology with hard and humanitarian sciences. It will be an intellectual instrument for overcoming the appeared challenges. The article discusses five vulnerabilities appearance is caused by the emergence of a complex society.